Digitalisasi Dan Literasi Kesehatan Pada Smart Village - Yulita Sirinti Pongtambing; Eliyah A M Sampetoding; Rafika Uksi; Esther Sanda Manapa (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
This study aims to examine the relationship between Digitalization and Health Literacy in the context of a Smart Village through a literature review method. The results of the literature analysis indicate that both play an integral role in the development of a Smart Village. Through this approach, the research details the positive implications of digitalization and health literacy on rural communities. Research recommendations include direct application of villages to assess community understanding and test the implementation of digital technology. This study provides an initial conceptual foundation to support the development of a sustainable Smart Village.